Congruency analysis of species ranking based on leaf traits: which traits are the more reliable? - Roche, Philip; Díaz-Burlinson, Natalia; Gachet, Sophie (Plant Ecology formerly `Vegetatio', 2004)
Nine leaf traits area, fresh weight, dry weight, volume, density, thickness, speciﬁc leaf area SLA, dry matter content LDMC, leaf nitrogen content LNC from ten plant species at eight sites in southern mediterranean France were investigated in order to assess their variability along a climatic gradient and their ranking congruency power. After examination of trait correlation patterns, we reduced the nine initial leaf traits to four traits, representative of three correlation groups: allometric traits dry weight, functional traits SLA and dry matter percentage and Leaf Thickness. We analysed the variability of these four leaf traits at species and site level. We observed that between species variation between 64.5 for SLA and 91% for LDMC is higher than within species variation. Allowing a good congruency of species ranking assessed by spearman rank correlation and a good reallocation of individuals to species by discriminant analysis. A site level variability between 0.7% for Dry weight and 6.9% for SLA was identiﬁed and environmental parameters altitude, temperature, precipitation, nitrogen, pH were considered as probable control factors. We found signiﬁcant correlation between SLA, LDMC and the average minimum temperature respectively r0.87 and r-0,9 and no correlation for the other traits or environmental parameters. Furthermore, we conclude that two leaf traits appear to be central in describing species: speciﬁc leaf area SLA, percentage of dry matter LDMC. While, SLA and LDMC are strongly correlated, LDMC appears to be less variable than SLA. According to our results the Dry Matter Content or its reversal Leaf Water Content appears the best leaf trait to be quantiﬁed for plant functional screening. Leaf thickness appeared to be rather uncorrelated with other leaf traits and show no environmental contingency; its variability could not have been explained in this study. Further studies should focus on this trait.
Keywords: dry matter content; France; Mediterranean; sla

Congruency analysis of species ranking based on leaf traits: which traits are the more reliable? - Roche, Philip; Díaz-Burlinson, Natalia; Gachet, Sophie (Plant Ecology formerly `Vegetatio', 2004)
Nine leaf traits area, fresh weight, dry weight, volume, density, thickness, speciﬁc leaf area SLA, dry matter content LDMC, leaf nitrogen content LNC from ten plant species at eight sites in southern mediterranean France were investigated in order to assess their variability along a climatic gradient and their ranking congruency power. After examination of trait correlation patterns, we reduced the nine initial leaf traits to four traits, representative of three correlation groups: allometric traits dry weight, functional traits SLA and dry matter percentage and Leaf Thickness. We analysed the variability of these four leaf traits at species and site level. We observed that between species variation between 64.5 for SLA and 91% for LDMC is higher than within species variation. Allowing a good congruency of species ranking assessed by spearman rank correlation and a good reallocation of individuals to species by discriminant analysis. A site level variability between 0.7% for Dry weight and 6.9% for SLA was identiﬁed and environmental parameters altitude, temperature, precipitation, nitrogen, pH were considered as probable control factors. We found signiﬁcant correlation between SLA, LDMC and the average minimum temperature respectively r0.87 and r-0,9 and no correlation for the other traits or environmental parameters. Furthermore, we conclude that two leaf traits appear to be central in describing species: speciﬁc leaf area SLA, percentage of dry matter LDMC. While, SLA and LDMC are strongly correlated, LDMC appears to be less variable than SLA. According to our results the Dry Matter Content or its reversal Leaf Water Content appears the best leaf trait to be quantiﬁed for plant functional screening. Leaf thickness appeared to be rather uncorrelated with other leaf traits and show no environmental contingency; its variability could not have been explained in this study. Further studies should focus on this trait.
Keywords: dry matter content; France; Mediterranean; sla

Functional groups in phytoecology: an application to the study of isolated plant communities in Mediterranean France - Médail, F; Roche, Philip; Tatoni, Thierry (Acta Oecologica, 1998)
e main objective of this study is to compare functional patterns versus plant composition in holm-oak forest isolates from two sites of Provence (Mediterranean France), on siliceous (Maures) or calcareous substrates (Luberon). In order to define plant functional groups, 9 traits out of a total of 71 attributes, were used. Twenty functional groups were defined with predominantly vegetative traits. Within each site, edges and forested core areas refer to different functional groups, in relation to the isolate structure and disturbance effects. In siliceous Provence, a higher structural and functional diversity occurs inside isolates, whereas on calcareous substrate, the diversity of plant functional groups which charac- terizes edges, is as important as in internal parts of isolates. Functional diversity does not necessarily follow the same patterns as the specific diversity, which is always greater in edges. Thus, the use of some sets of attributes, resulting from evolutionary trade-off between plants and their environment, can provide a better understanding of ecological consequences of disturbances. 0
Keywords: biological conservation; disturbances; ecosystems; fragmentation; functional diversity; Functional groups; Mediterranean-type ecosystems; terrestrial islands